H.G. Wells - Young, Kenneth (Writers and Their Work Series., 1970)
In this 1974 study, Kenneth Young reviews H.G. Wells's development first as a creator of scientific romances, then as a writer of semi-autobiographical fiction, and finally as a publicist and prophet of world affairs.